Elemental Analysis of Indian Green and Black Tea Leaves Using Hand Held X-Ray Fluorescence Spectrometer - Denni, Mammen; Joseph, Daisy; Ayesha, Ghanchi (International Journal For Research In Agricultural And Food Science, 2019)
Green and black tea samples available in Indian markets were analyzed for their elemental composition using Hand held X-ray Fluorescence spectrometer. Twenty eight elements were analyzed in the tea leaves. Macronutrients detected in major proportions were K and Ca, while Zn, Fe, Cu, Mn, and Mg were the micronutrients detected in all the samples. Si, P and S were the nonmetals detected in the tea leaves. The samples also showed presence of rare earth metals like Ag, Sr, Rb, Nb and Mo.